Automatic graph-based method for localization of cochlear implant electrode arrays in clinical CT with sub-voxel accuracy - Zhao, Yiyuan; Chakravorti, Srijata; Labadie, Robert F.; Dawant, Benoit M.; Noble, Jack H. (Medical image analysis, 2019)
•Cochlear implant programming relies on the intra-cochlear locations of electrodes.•An automatic method to segment electrode arrays in post-implantation CTs.•It uses two graph-based path-finding algorithms to segment CI electrodes in CTs.•The accuracy of the method is close to the manual localizations produced by experts.•The method is robust with respect to various CT acquisition parameters. Cochlear implants (CIs) are neural prosthetics that provide a sense of sound to people who experience severe to profound hearing loss. Recent studies have demonstrated a correlation between hearing outcomes and intra-cochlear locations of CI electrodes. Our group has been conducting investigations on this correlation and has been developing an image-guided cochlear implant programming (IGCIP) system to program CI devices to improve hearing outcomes. One crucial step that has not been automated in IGCIP is the localization of CI electrodes in clinical CTs. Existing methods for CI electrode localization do not generalize well on large-scale datasets of clinical CTs implanted with different brands of CI arrays. In this paper, we propose a novel method for localizing different brands of CI electrodes in clinical CTs. We firstly generate the candidate electrode positions at sub-voxel resolution in a whole head CT by thresholding an up-sampled feature image and voxel-thinning the result. Then, we use a graph-based path-finding algorithm to find a fixed-length path that consists of a subset of the candidates as the localization result. Validation on a large-scale dataset of clinical CTs shows that our proposed method outperforms the state-of-art CI electrode localization methods and achieves a mean error of 0.12 mm when compared to expert manual localization results. This represents a crucial step in translating IGCIP from the laboratory to large-scale clinical use. [Display omitted]